Marxism and democracy - Femia, Joseph V. (Marxist introductions., 1993)
The collapse of the Soviet Union sounded the death knell for Marxism as a blueprint for social change. Why has this doctrine failed in its grand ambition to liberate the human race from poverty and oppression? This analysis of what Marx and his disciples had to say about democracy sheds light on the reasons for this failure.